Tailoring porosity and mechanical properties of wire-based directed energy deposited molybdenum alloys through hot isostatic pressing - Karim, Md Abdul; Tanvir, Gazi; Jadhav, Sainand; Islam, Saiful; Kim, Young Min; Villarraga-Gomez, Herminso; Lee, Ho Jin; Jeon, Yongho; Kim, Duck Bong (Applied Materials Today, 2025)
Additive manufacturing of molybdenum alloys holds great potential for various applications in extreme environments, yet challenges such as internal porosity and mechanical properties refinement remain largely unexplored. This study pioneers the use of hot isostatic pressing (HIP) to treat wire-based, directed energy-deposited titanium-zirconium-molybdenum (TZM), a widely used molybdenum alloy, addressing porosities formed during fabrication. Two distinct HIP conditions were investigated: one at 1200 °C and the other at 1500 °C, both applied under 200 MPa of pressure for 180 mins. Porosity measurements, conducted using optical microscopy and 3D X-ray microscopy, revealed that HIP treatment at 1200 °C reduced the pore volume fraction from 5.3 % to 4.2 %. In contrast, treatment at 1500 °C was highly effective in eliminating pores, reducing the fraction to 1.7 %. The higher temperature also promoted recrystallization, particularly near pore regions, resulting in a columnar-to-equiaxed grain transformation. Calculation of phase diagram (CALPHAD)-based modeling was employed to characterize the evolution of oxide and carbide secondary phases, such as ZrO2 and (Ti,Zr)C precipitates, which were undetectable in X-ray diffraction spectra due to their very low content (< 1.0 wt. %) in the alloy. HIP treatment improved the mechanical properties of the fabricated specimens, with ultimate tensile strength and elongation progressively increasing at higher HIP temperatures, attributed to the enhanced pore recovery. Specimens exhibited a significant increase in strength (approximately 127 %), rising from 162 ± 36 MPa to 368 ± 21 MPa after HIP treatment at 1500 °C. Elongation improved from 1.48 ± 0.11 % to 1.84 ± 0.08 %.
Keywords: Directed energy; Directed energy deposition; Energy depositions; Extreme environment; Hot-isostatic pressings; Internal porosity; Mechanical; Property; Recrystallisation; Strength; Directed energy deposition; Hot isostatic pressing; Molybdenum; Porosity; Recrystallization; Refractory metals; Strength